Ancient Moderns Greek Island art and culture, 2000-3000 B.C. [videorecording] - Bellin, Harvey; Cavander, Kenneth; Harrison, Rex.; Kieffer, Tom.; Ladas, Alexis ([S.l.] Global Concepts - The Media Group, 1979)
Discusses the Aegean or prehistoric civilization of the Greek island, also its art and culture.
VHS.
Narrator, Rex Harrison.
Script, Kenneth Cavander.
Keywords: Civilization, Aegean